2019
DOI: 10.1016/j.ceramint.2019.05.285
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural analysis and dielectric properties of the double-layer Aurivillius compound Pb1-2Bi1.5+2La0.5Nb2-Mn O9

Abstract: The double-layer Aurivillius phases Pb 1-2x Bi 1.5+2x La 0.5 Nb 2-x Mn x O 9 (x = 0, 0.1, 0.3, and 0.5) were synthesized by a molten salt method using a mixture of K 2 SO 4 /Na 2 SO 4 . The effect of composition on the structure, morphology and dielectric properties was investigated. X-ray diffraction showed that single-phase samples with a non-polar, orthorhombic A2 1 am structure were obtained for x = 0, 0.1 and 0.3. The unit cell becomes more orthorhombic with increasing x as the degree of distortion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 41 publications
6
23
0
1
Order By: Relevance
“…Furthermore, the Ti 4+ could be simultaneously substituted by Mn 3+ up to 15% molar ratio Ti 4+ with adjusted the Ca:Bi ratio as the nominal formula for x = 0.6. The substitution of Mn 3+ on the B-site cation up to 15% molar ratio has been reported in our previous reports both for four-layer Aurivillius Pb 1-x Bi 4+x Ti 4-x Mn x O 15 and double-layer Aurivillius Pb 1-2x Bi 1.5+2x La 0.5 Nb 2-x Mn x O 9 synthesized by the molten salt method 8,9 . The presence of impurities for x = 0.8 and 1 is suggested due to the oxidizing Mn 3+ to Mn 4+ in samples.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Furthermore, the Ti 4+ could be simultaneously substituted by Mn 3+ up to 15% molar ratio Ti 4+ with adjusted the Ca:Bi ratio as the nominal formula for x = 0.6. The substitution of Mn 3+ on the B-site cation up to 15% molar ratio has been reported in our previous reports both for four-layer Aurivillius Pb 1-x Bi 4+x Ti 4-x Mn x O 15 and double-layer Aurivillius Pb 1-2x Bi 1.5+2x La 0.5 Nb 2-x Mn x O 9 synthesized by the molten salt method 8,9 . The presence of impurities for x = 0.8 and 1 is suggested due to the oxidizing Mn 3+ to Mn 4+ in samples.…”
Section: Resultssupporting
confidence: 74%
“…The dielectric constant value at 100 kHz increases as x increases, where the value is 206.03, 342.4, 491.11, and 868.41 for x = 0, 0.2, 0.4, and 0.6, respectively. It was reported that the presence of A-site cations with 6s 2 lone pair electrons such as Bi 3+ strongly favors a highly distorted structure, resulting in increased polarization 8,20 . According to the nominal formula, the substitution of Mn 3+ for Ti 4+ on the B-site was compensated by the increasing proportion of Bi 3+ cations, which could result in the higher distortion of BO 6 octahedra.…”
Section: The Refined Lattice Parameters and Cell Volume Of Single-phamentioning
confidence: 99%
See 2 more Smart Citations
“…Referring to the ionic radius of Pb 2þ (1.49 Å) and Bi 3þ (1.31 Å) for 12-fold coordination and the ionic radii of Mn 3þ (0.645 Å) and Ti 4þ (0.605 Å) for 6-fold coordination [18,19], the decreased cell volume is strongly affected by the increasing proportion of smaller Bi 3þ and the decreasing proportion of larger Pb 2þ , according to the nominal formula of Pb 1-x Bi 3.5þx Nd 0.5 Ti 4-x Mn x O 15 . These compositional changes resulted in the higher distortion of the BO 6 octahedra, by which the structure becomes more orthorhombic [20,21]. This distortion led to the tilting of BO 6 octahedra along the a-axis, confirmed by the increased difference between the a and b lattice parameter [22].…”
Section: Resultsmentioning
confidence: 99%